Details of human middle ear morphology based on micro‐CT imaging of phosphotungstic acid stained samples. (22nd May 2015) - De Greef, Daniel; Buytaert, Jan A.N.; Aerts, Johan R.M.; Van Hoorebeke, Luc; Dierick, Manuel; Dirckx, Joris
ABSTRACT A multitude of morphological aspects of the human middle ear (ME) were studied qualitatively and/or quantitatively through the postprocessing and interpretation of micro‐CT (micro X‐ray computed tomography) data of six human temporal bones. The samples were scanned after phosphotungstic acid staining to enhance soft‐tissue contrast. The influence of this staining on ME ossicle configuration was shown to be insignificant. Through postprocessing, the image data were converted into surface models, after which the approaches diverged depending on the topics of interest. The studied topics were: the ME ligaments; morphometric and mechanical parameters of the ossicles relating to inertia and the ossicular lever arm ratio; the morphology of the distal incus; the contact surface areas of the tympanic membrane (TM) and of the stapes footplate; and the thickness of the TM, round window of the cochlea, ossicle joint spaces, and stapedial annular ligament. Some of the resulting insights are relevant in ongoing discussions concerning ME morphology and mechanical functions, while other results provide quantitative data to add to existing data. All findings are discussed in the light of other published data and many are relevant for the construction of mechanical finite element simulations of the ME. J. Morphol. 276:1025–1046, 2015. © 2015 Wiley Periodicals, Inc.